A new species of Pamphagus (Orthoptera: Pamphagidae) from Algeria with a key to all the species of the genus - Benkenana, Naima; Massa, Bruno (Zootaxa, 2017)
The authors describe Pamphagus milevitanus n. sp. occurring in the North and South highlands of Constantine, in Mila, Setif and Oum-el Bouaghi provinces, where it is fairly common. They compare the characters of this species with those of the most related species of the genus and present a complete plate and a key to all the species of the genus Pamphagus known to date.